1982
DOI: 10.1002/cne.902040302
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of somatostatin‐containing neuron system of the rat: Immunohistochemical analysis. II. Forebrain and diencephalon

Abstract: The ontogeny of the somatostatin (SRIF) neuron system in the forebrain and diencephalon the rat was investigated by means of the indirect immunofluorescence method. SRIF-positive cells first appear in the primordium of the hypothalamus surrounding the fasciculus mammillothalamicus of the fetus at gestational day 14 (10-12-mm embryo). At gestational days 16-17 (14-17-mm embryo, SRIF-positive cells appear in the developing piriform cortex and entopeduncular nucleus. The fetus at gestational days 18-19 (17-26-mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(44 citation statements)
references
References 30 publications
5
39
0
Order By: Relevance
“…It has been reported that SS may participate in the differentiation and development of tissues (Wang et al, 1995). During development of the forebrain and diencephalon in mouse, SRIF-positive cells first appear in the primordium of the hypothalamus at gestational day 14, then remarkably increase in number in various forebrain and diencephalic areas at gestational days 18-19, and sequentially increase in number during the perinatal stage (Shiosaka et al, 1982). Furthermore, preproCST reaches a maximum level in the cortical areas of mouse during the second post-natal week, which correlates with the maturation of cortical interneurons (de Lecea et al, 1997).…”
Section: A B Cmentioning
confidence: 92%
“…It has been reported that SS may participate in the differentiation and development of tissues (Wang et al, 1995). During development of the forebrain and diencephalon in mouse, SRIF-positive cells first appear in the primordium of the hypothalamus at gestational day 14, then remarkably increase in number in various forebrain and diencephalic areas at gestational days 18-19, and sequentially increase in number during the perinatal stage (Shiosaka et al, 1982). Furthermore, preproCST reaches a maximum level in the cortical areas of mouse during the second post-natal week, which correlates with the maturation of cortical interneurons (de Lecea et al, 1997).…”
Section: A B Cmentioning
confidence: 92%
“…During development, somatostatin-expressing cells in the central nervous system appear first in the primordium of the E14 hypothalamus, and other telencephalic regions are recruited later (12,13,15,16). As the central nervous system develops, somatostatin is expressed in differentiating neurons as well as in glial cells, but the number of somatostatin-positive cells fluctuates.…”
Section: Mol Endo · 1998mentioning
confidence: 99%
“…Primary cultures of cells from developing cerebral cortex and hippocampus, two brain regions that contain somatostatinproducing neurons (12), were prepared from E16 fetuses removed from timed-pregnant Sprague Dawley rats. After careful removal of the meningeal membranes, the cerebral cortex was separated from the rest of the brain, and the developing hippocampi were dissected as described (58).…”
Section: Establishment Of Immortalized Forebrain-derived Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, no NTI cells were noted in the vm at any of the stages examined. Somatostatin-like immunoreactive (SOMI) structures : SOMI fibers appeared first in vm at gestational day 19 (21). At this stage, a few SOMI cells were seen around the vm but not within the vm.…”
mentioning
confidence: 99%